2010
DOI: 10.1111/j.1398-9995.2010.02483.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles derived from Staphylococcus aureus induce atopic dermatitis-like skin inflammation

Abstract: BackgroundRecently, we found that Staphylococcus aureus produces extracellular vesicles (EV) that contain pathogenic proteins. Although S. aureus infection has been linked with atopic dermatitis (AD), the identities of the causative agents from S. aureus are controversial. We evaluated whether S. aureus-derived EV are causally related to the pathogenesis of AD.MethodsExtracellular vesicles were isolated by the ultracentrifugation of S. aureus culture media. The EV were applied three times per week to tape-stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
221
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(228 citation statements)
references
References 23 publications
4
221
0
3
Order By: Relevance
“…Proteomic analysis revealed that extracellular vesicles derived from S. aureus harbor several pathogenic components (10). Furthermore, S. aureus extracellular vesicles induce atopic dermatitislike skin inflammation in mice (47). These observations provide hints on the possible roles of Gram-positive secreted vesicles as vaccine candidates (10).…”
Section: Discussionmentioning
confidence: 76%
“…Proteomic analysis revealed that extracellular vesicles derived from S. aureus harbor several pathogenic components (10). Furthermore, S. aureus extracellular vesicles induce atopic dermatitislike skin inflammation in mice (47). These observations provide hints on the possible roles of Gram-positive secreted vesicles as vaccine candidates (10).…”
Section: Discussionmentioning
confidence: 76%
“…In addition, our previous work indicates that EVs in indoor dust are important in the development of neutrophilic inflammation in the lung (11). Previously, we also found that the Grampositive bacterium S. aureus produces EVs (9), which may be causally related to atopic dermatitis in the skin (28) and also neutrophilic inflammation in the lung (12). The present study showed that the repeated inhalation of E. coli EVs induced neutrophilic inflammation and thereby emphysema mainly via an IL-17A-dependent mechanism.…”
Section: Discussionmentioning
confidence: 54%
“…При этом продукция ТСЛП от-менялась при подавлении активации TLR2 и TLR6 специфическими ингибиторами, что показывает прямую связь повышения уровня ТСЛП с распозна-ванием липопротеинов бактерии. S. aureus также по-вышает уровень экспрессии ТСЛП в фибробластах кожи [36]. Выброс ТСЛП наблюдается также и в от-вет на дрожжеподобные грибы Malassezia, являю-щиеся вторым по значимости микроорганизмом, колонизирующим кожу больных с аллергодермато-зами.…”
Section: механизмы контроля целостности барьеров организма млекопитающихunclassified